2022
DOI: 10.1590/0102-311xen057222
|View full text |Cite
|
Sign up to set email alerts
|

Time trends of physical activity for leisure and transportation in the Brazilian adult population: results from Vigitel, 2010-2019

Abstract: This time-series study examined a 10-year historical series of the physical activity prevalence for leisure and transportation in the Brazilian adult population. Information from 512,969 adults interviewed from the Vigitel between 2010 and 2019 was analyzed. Individuals who reported practicing at least 150 minutes/week of moderate-intensity physical activity or at least 75 minutes/week of vigorous-intensity physical activity were considered active during leisure time. Individuals who reported walking or cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The findings showed that men, young people, and people with high levels of education had the highest incidence of leisure-time physical activity. [ 43 ] Unsurprisingly, the current study found lower engagement among CAMS undergraduates. This might be due to the fact that the healthcare students in the current study spent a lot of their leisure time engaging in study-related activities and spending a lot of time in hospitals performing clinical rotations or practical cessations.…”
Section: Discussionmentioning
confidence: 51%
“…The findings showed that men, young people, and people with high levels of education had the highest incidence of leisure-time physical activity. [ 43 ] Unsurprisingly, the current study found lower engagement among CAMS undergraduates. This might be due to the fact that the healthcare students in the current study spent a lot of their leisure time engaging in study-related activities and spending a lot of time in hospitals performing clinical rotations or practical cessations.…”
Section: Discussionmentioning
confidence: 51%
“…In several Brazilian states, there was also a decrease in stroke mortality rates for both sexes [ 6 , 12 ]. This decrease in stroke mortality rates may be due to government policies designed to control factors associated with stroke [ 21 , 22 , 23 ]. Furthermore, in on-site observation, the implementation of a specialized health unit for the treatment of stroke patients in the metropolitan area of Greater Victoria may have improved the diagnosis of stroke and prevented death.…”
Section: Discussionmentioning
confidence: 99%